2019
DOI: 10.4049/jimmunol.1801112
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Microenvironment Modulates Immunological Outcomes of Myeloid Cells with mTORC1 Disruption

Abstract: The role of the mTOR signaling pathway in different myeloid cell subsets is poorly understood in the context of tumor development. In this study, myeloid cell-specific Raptor knockout (KO) mice were used to determine the roles of mechanistic target of rapamycin complex 1 (mTORC1) in regulating macrophage function from Lewis lung carcinoma (LLC) s.c. tumors and lung tumor metastasis. We found no difference in tumor growth between conditional Raptor KO and control mice in the s.c. tumor models, although depletio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…Inflammatory factors such as prostanoids and TNFα can drive myeloid cells toward functions as aggressive phagocytic killing cells [ 15 , 16 ]. Tumor cells that can produce these same factors may be able to alter the signaling effects on myeloid cells in their microenvironment, possibly by using different localized concentrations or timing [ 13 , 14 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Inflammatory factors such as prostanoids and TNFα can drive myeloid cells toward functions as aggressive phagocytic killing cells [ 15 , 16 ]. Tumor cells that can produce these same factors may be able to alter the signaling effects on myeloid cells in their microenvironment, possibly by using different localized concentrations or timing [ 13 , 14 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…While these type 2 stimuli play a role in the response to parasites and allergy, they are also major drivers of wound healing; in line with this, IL-4 and IL-13-stimulated macrophages have been wellcharacterized to adopt gene expression profiles associated with wound-healing and anti-inflammatory macrophage phenotypes [68][69][70][71]. As such, these macrophages are often used as a model to study protumorigenic macrophages in vitro and are often referred to as 'M2' macrophages; throughout this paper, we will refer to IL-4 and IL-13-stimulated macrophages as pro-resolution macrophages [66,72,73].…”
Section: Macrophages Of Different Phenotypes Exhibit Different Circad...mentioning
confidence: 90%
“…In addition, Raptor also regulates Th1 cell differentiation and function via other unknown mechanisms. Researchers have found that the decreased Th1 T cell response in the s.c. TME was observed in tumor-bearing Raptor conditional knockout (cKO) mice while the detailed mechanism still requires further research ( 104 ).…”
Section: Raptor Mediates Th 1 and Th 17 Cell Differentiation Via Bind...mentioning
confidence: 99%